A detailed investigation of low latitude tweek atmospherics observed by the WHU ELF/VLF receiver: 2. Occurrence features and associated ionospheric parameters. Issue 3 (8th June 2020) - Yi, Juan; Gu, XuDong; Cheng, Wen; Tang, XinYue; Chen, Long; Ni, BinBin; Zhou, RuoXian; Zhao, ZhengYu; Wang, Qi; Zhou, LiQing
Abstract : As a companion paper to Zhou RX et al. (2020), this study describes application of the automatic detection and analysis module to identify all the tweek atmospherics detectible in the WHU ELF/VLF receiver data collected at Suizhou station during the period of 3 February through 29 February 2016. Detailed analysis of the identified low‐latitude tweek events reveals that the occurrence rate varies considerably — from 800 to 6000 tweeks per day, and exhibits a strong diurnal and local time dependence, the peak occurring before local midnight. The diurnal variation of identified tweeks was similar to that of the lightning data obtained by the World‐Wide Lightning Location Network (WWLLN).. Estimates of the propagation distance and ionospheric reflection height of tweek atmospherics suggest that the majority (~92%) of the low latitude tweeks originate from the lightning activity within a radius of 4000 km and that they are very likely to reflect from the lower ionospheric D‐region at the height range of 75–85 km. At these lower ionospheric reflection altitudes, ~74% of the corresponding electron densities from the tweek spectral measurements are within 24.5–27.5 cm ‐3 . The daily variation of estimated D‐region electron densities in the considered period (February 2016) also exhibits a small overall increasing trend from early to later in the month.